Nonsense-Mediated Decay of Human HEXA mRNA - Rajavel, Kavitha S. (American Society for Microbiology, 2001)
Nonsense-mediated mRNA decay (NMD), the loss of mRNAs carrying premature stop codons, is a process by which cells recognize and degrade nonsense mRNAs to prevent possibly toxic effects of truncated peptides. Most mammalian nonsense mRNAs are degraded while associated with the nucleus, but a few are degraded in the cytoplasm; at either site, there is a requirement for translation and for an intron downstream of the early stop codon. We have examined the NMD of a mutant HEXA message in lymphoblasts derived from a Tay-Sachs disease patient homozygous for the common frameshift mutation 1278ins4. The mutant mRNA was nearly undetectable in these cells and increased to approximately 40% of normal in the presence of the translation inhibitor cycloheximide. The stabilized transcript was found in the cytoplasm in association with polysomes. Within 5 h of cycloheximide removal, the polysome-associated nonsense message was completely degraded, while the normal message was stable. The increased lability of the polysome-associated mutant HEXA mRNA shows that NMD of this endogenous mRNA occurred in the cytoplasm. Transfection of Chinese hamster ovary cells showed that expression of an intronless HEXA minigene harboring the frameshift mutation or a closely located nonsense codon resulted in half the normal mRNA level. Inclusion of multiple downstream introns decreased the abundance further, to about 20% of normal. Thus, in contrast to other systems, introns are not absolutely required for NMD of HEXA mRNA, although they enhance the low-HEXA-mRNA phenotype.